-14-8x=2(3x+7)

Simple and best practice solution for -14-8x=2(3x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14-8x=2(3x+7) equation:



-14-8x=2(3x+7)
We move all terms to the left:
-14-8x-(2(3x+7))=0
We calculate terms in parentheses: -(2(3x+7)), so:
2(3x+7)
We multiply parentheses
6x+14
Back to the equation:
-(6x+14)
We get rid of parentheses
-8x-6x-14-14=0
We add all the numbers together, and all the variables
-14x-28=0
We move all terms containing x to the left, all other terms to the right
-14x=28
x=28/-14
x=-2

See similar equations:

| 3x+12=4x-(2x-5) | | 4=-2(3x+1)+2 | | -1/2(12v-20)+4=-12 | | 192=(-8+8x) | | 1/1.18=83/x | | 83/x=1/1.18 | | 3x+6+7x+3=10 | | 5912+2x+1=59 | | 6x-74x-1=360 | | 24+0.14x=0.18x | | 2(7.5x)=83 | | 8q+7=5q=11 | | 192=8(8+8x) | | X/3600x703=20.5 | | .2x+21=6 | | 2+3.50g=5×+3.25g | | 1,000-1,200m=1,500-1,175m | | 1,000+1,200m=1,500+1,175 | | 1,000-1,200m=1,500-1,200m | | 6.5x+2(10)=4(x+10) | | 35-20y=1-3y | | (3x+60)=(6x+30)= | | 2(x-2)=36/9 | | 4(x+10-1/2x)=-2x+48 | | 20=0+1/2(9.81)t^2 | | 20l+45=225 | | -11=n-17 | | b+28+b-28+33=180 | | 30x-2=900 | | 3x-20=6+x | | 7=3-(2m-8) | | 5x²-181=-1 |

Equations solver categories